Edukasi dan Implementasi Teknologi Digital pada UMKM Klinik Hewan: Studi Kasus Zenith Animal Care - Fitriana, Nur; Jumiati, Ami; Tantra, Yogi Surya; Lubis, Indah Mawaddah; Gozali, Valensia Bertha; Meldiana, Nadia (LPPI UMN AL WASHLIYAH, 2025)
This community service activity aims to improve operational and financial efficiency for MSMEs engaged in animal health services, namely Zenith Animal Care Animal Clinic, located in Pekanbaru. Previously, this clinic did not have a digital system for managing patients' medical records, cashier applications, and modern payment systems, which resulted in low service efficiency and accountability of financial transactions. In this activity, the service team provided education and assistance in the use of the SIMRAISHA application as a digital medical record system and integrated cashier system, as well as implementing QRIS-based digital payment methods. In addition, the team also helps compile price lists for clinic services so that price information is more transparent and easily accessible to customers. The method of the activity was carried out through a participatory approach, direct training, and evaluation of implementation results for two weeks. The results of this activity show that the partners are able to operate both applications independently, as well as an increase in transaction time efficiency and ease of tracking veterinary medical records. The use of QRIS also provides ease of payment for customers who were previously limited to cash methods. This activity shows the importance of education on the digitization of operational systems for health service MSMEs as part of strengthening the digital economy